The Role of Eco – Innovation in Mediating The Relationship Between Financial Literacy and Sustainability of UMKM in Central Java - Fabribda, Laily Hasanah; Winarsih, Winarsih (Jurnal Penelitian Ekonomi dan Bisnis, 2025)
The micro, small, and medium enterprises sector is the driving force of a country's economy, but along with the times there are still many problems that occur and have not been resolved, one of which is financial knowledge and innovations. The purpose of this study is to investigate and test the sustainability of MSMEs with Financial Literacy and Innovation. Study This uses a quantitative approach, research data in the form of primary data through questionnaires and taking population as well as research samples from the actors or managers of MSMEs as many as 433 respondents. The sampling method used was purposive sampling technique. The independent variable in this study is financial literacy, the intervening variable is eco-innovation and the dependent variable is the sustainability of MSMEs. The method used in analyzing the data is simple linear regression analysis with SPSS version 24 software. The results of the classical assumption test are normal, multicollinearity does not occur, heteroscedasticity does not occur. The results of this study prove that financial literacy has a significant positive effect on the sustainability of MSMEs, and financial literacy has a significant positive effect on eco-innovation. Meanwhile, eco - innovation has a significant positive effect on the sustainability of MSMEs, and eco - innovation has a positive and insignificant effect in mediating financial literacy on the sustainability of MSME.